Monetary Policy Impact on the Capital Market: Evidence from Armenia - Teryan, Diana («Տնտեսագետ» հրատ․)
The main aim of this research is to study the impact monetary policy has on different segments of the capital market in the Republic of Armenia. In the frame of the paper, we investigated the relationship between monetary indicators and government bond, corporate bond, and stock markets. We designed and estimated a structural vector autoregressive model using a monthly dataset of six variables describing the monetary policy of the Central Bank of Armenia and different segments of the capital market. Based on the model, we forecasted baseline and alternative scenarios to compare the results with the actual indicators. In addition, we conducted impulse response and forecast error variance decomposition analyses. The research results showed that our model was generally able to predict the key trends in the observed capital markets over the projection period. According to the alternative forecast scenario, tighter monetary policy with a more aggressive interest rate hike would have led to higher volatility in government, corporate bonds, and stock markets in Armenia. The outcomes of the conducted analyses suggested that monetary policy had a stronger relationship with the government bond market, while its interactions with the corporate bond and stock markets were mostly insignificant in Armenia.
Keywords: Finance